Dispositional and situational empathy in Parkinson's disease and their relationship with cognition - Alonso-Recio, Laura; Mendoza, Liz; Pérez, África; Rubio, Sandra; Serrano, Juan Manuel (Frontiers in Psychology, 2025)
IntroductionParkinson's disease (PD) affects not only motor function but also social cognition, particularly empathy. While most studies focus on dispositional empathy—an automatic, stable trait measured by self-report—situational empathy, assessed in specific contexts, has been barely explored. The relationship between these empathy types and their link to cognitive functioning in PD are largely unknown. This study examines dispositional and situational empathy in PD patients, considering cognitive impairment as a moderating factor.MethodThe sample included 31 cognitively preserved PD patients (MoCA ≥ 26), 39 cognitively impaired PD patients (MoCA < 26), and 33 age-matched healthy controls. Dispositional empathy was assessed with the Interpersonal Reactivity Index. Situational empathy was evaluated through a behavioral task where participants viewed dynamic emotional faces paired with emotionally charged sentences, and selected the emotion they felt. A comprehensive neuropsychological battery assessed cognitive functioning.ResultsNo group differences emerged in dispositional empathy. However, cognitively impaired PD patients showed poorer situational empathy compared to the other groups. No significant correlation was found between dispositional and situational empathy, nor consistent correlations between empathy and specific cognitive processes.DiscussionFindings show that PD affects empathy unevenly: dispositional empathy is preserved, but situational empathy declines with cognitive impairment. This suggests that empathy deficits depend on task complexity and overall cognitive status, not just isolated functions. Since situational empathy requires real-time processing of emotional and contextual cues, it is especially sensitive to cognitive decline. These results highlight the need for comprehensive assessments to reflect PD's neurocognitive variability.